Diseño e implementación de un sistema de monitoreo y control ambiental basado en IoT para optimizar la producción de huevos - Obando Morillo, Jonathan Fabian (2023)
The system implemented to improve poultry egg production is based on environmental monitoring and control through IoT. This system uses commercially available materials and consists of a microcontroller that captures and processes environmental variables, which play a crucial role in egg production. In addition, a microcomputer is incorporated that provides additional services that traditional incubators do not have. This allows Internet connection and turning it into an IoT device that can be monitored and controlled remotely. The project is developed using a non-experimental methodology, which allows observing the phenomena that occur during the incubation process without directly intervening in the object of study. To collect the data, the observation technique is used, which helps to identify the behavior of the object of study in a non-intrusive way, in two samples made with a population of 55 chicken eggs, it is shown that the developed prototype obtained greater productivity, achieving 30% incubation efficiency compared to 0% for HDD mini 56S incubator. In summary, the implemented system, based on IoT, shows significant improvements in poultry egg production. The results obtained in the tests carried out demonstrate the efficiency of the developed prototype in comparison with a conventional incubator, highlighting its monitoring capacity and remote control through an Internet connection.